2018
DOI: 10.3390/rs11010018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Effects of SAR Imaging Parameters and Environmental Conditions on the Standard Deviation of the Co-Polarized Phase Difference Measured over Sea Surface

Abstract: This study aimed at analyzing the effect of Synthetic Aperture Radar (SAR) imaging parameters and environmental conditions on the standard deviation of the co-polarized phase difference (sjC ) evaluated over sea surface[...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…σ φ CO has been found to increase with the presence of oil (see, e.g., [54]- [57]), and this behavior was according to [54], [55] explained by the different scattering process (Bragg vs. non-Bragg) between clean sea and oil. Some studies have showed that the broadening of φ CO could be due to system noise (see, e.g., [10], [16], [43]). Minchew et al [10] discovered no difference between the σ φ CO for oil and clean sea except in the presence of instrument noise for one UAVSAR scene.…”
Section: Scattering Properties and Polarimetric Sar Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…σ φ CO has been found to increase with the presence of oil (see, e.g., [54]- [57]), and this behavior was according to [54], [55] explained by the different scattering process (Bragg vs. non-Bragg) between clean sea and oil. Some studies have showed that the broadening of φ CO could be due to system noise (see, e.g., [10], [16], [43]). Minchew et al [10] discovered no difference between the σ φ CO for oil and clean sea except in the presence of instrument noise for one UAVSAR scene.…”
Section: Scattering Properties and Polarimetric Sar Featuresmentioning
confidence: 99%
“…When studying oil slicks with SAR, multiplicative noise has traditionally not been considered (see, e.g., [5], [10], [13]- [16]). The multiplicative noise raises the noise floor, hence reducing the overall SNR in the data.…”
Section: Introductionmentioning
confidence: 99%
“…The curve for targets under the multi-polarimetric feature set selected based on the J–M distance presents its own trend characteristics. However, previous studies have concluded that, in reality, the polarimetric characteristics performance of an oil slick are affected by factors including SAR system acquisition parameters (e.g., incident angles, NESZ, and resolution), ocean environmental conditions (e.g., wind speed/direction, sea currents, waves, sea temperature, and seawater composition), and intrinsic oil slick information (e.g., thickness, oil type, weathering degree, and cause of formation) [2,15,19,29,59,60,61]. Therefore, considering the situation described above, the proposed method uses statistical analysis to select the mean of the target sample region in order to construct the multi-polarimetric features model.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the standard deviation of the CPD has been shown almost independent of the estimation window size and unbiased when low correlation of co-polarized channels applies [19,20]. It is important to highlight that the std CPD behavior is affected by incidence angle, noise equivalent sigma zero (NESZ), and meteo-marine conditions as discussed by [21][22][23].…”
Section: Introductionmentioning
confidence: 95%